2009
DOI: 10.1158/1055-9965.epi-09-0171
|View full text |Cite
|
Sign up to set email alerts
|

Uptake of Risk-Reducing Surgery in Unaffected Women at High Risk of Breast and Ovarian Cancer Is Risk, Age, and Time Dependent

Abstract: Purpose: The uptake of risk-reducing surgery in women at increased risk of breast and ovarian cancer is highly variable between countries and centers within countries. We have investigated the rate, timing, and age of uptake of surgery in the northwest of England to report the results after up to 7 years in a Regional Genetics center. Methods: Uptake was documented in 211 known unaffected BRCA1/2 mutation carriers from 509 families and in 3,515 women at >25% lifetime risk of breast cancer without known mutatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
109
6
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 133 publications
(132 citation statements)
references
References 41 publications
14
109
6
3
Order By: Relevance
“…Our findings demonstrate that women with offspring are more likely to opt for RRSO; this result is consistent with other studies, which found that not having children was associated with delaying surgery [9,28]. The observed association between having offspring and uptake of RRSO is of course not surprising, given that RRSO results in irreversible infertility, and is therefore unlikely to be attractive to women who have not yet had children or those who are parous but are uncertain about whether to have more children.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our findings demonstrate that women with offspring are more likely to opt for RRSO; this result is consistent with other studies, which found that not having children was associated with delaying surgery [9,28]. The observed association between having offspring and uptake of RRSO is of course not surprising, given that RRSO results in irreversible infertility, and is therefore unlikely to be attractive to women who have not yet had children or those who are parous but are uncertain about whether to have more children.…”
Section: Discussionsupporting
confidence: 93%
“…[8], and being a carrier of a BRCA1 or BRCA2 mutation, e.g. [7,9]. However, almost no empirical evidence is available on the psychological determinants of the decision to undertake RRSO.…”
Section: Introductionmentioning
confidence: 99%
“…[19][20][21][22] Choosing RRBSO appears to be related to older age, perceived cancer risk, and perceived benefit of surgery. [99][100][101][104][105][106] In a 2012 long-term outcome study, Schwartz et al observed that >80% of BRCA1/BRCA2 carriers had undergone RRM, or RRBSO, or both at approximately 5 years after testing. Carriers also were more likely to have received breast cancer chemoprevention and breast magnetic resonance imaging screening.…”
Section: Hbocmentioning
confidence: 99%
“…the disadvantage of rrSo is a premature menopause and iatrogenic fertility, and therefore, it is recommended not to be performed earlier than the age of close to 40 years (4). young mutation carriers benefit most from riskreducing surgery (19). In older age groups, the breasts are generally easier to follow up, and the patients are less likely to choose surgical risk-reduction (20).…”
Section: Reconstruction N=27mentioning
confidence: 99%